From blue to red color wavelength complex modulation characteristics of liquid crystal on a metasurface device - Yong-Hae Kim; Kyunghee Choi; Jaehyun Moon; Jong-Heon Yang; Jae-Eun Pi; Ji Hun Choi; Chi-Sun Hwang; Jeong-Seon Yu; Jong-Hyun Kim (Scientific Reports)
Abstract Full-color wavelength complex modulations are essential to usher in the era of holographic displays. Although metasurfaces have been developed for passive holograms, only a limited number of active metasurfaces capable of complex modulation in the visible wavelength range have been reported. In this study, we successfully optimized a liquid crystal on a metasurface device to achieve complex reflectivity modulation for the first time. Specifically, we achieved complete phase modulation over $$2π$$ and amplitude modulation in the range of 0.3–0.6 at blue and green wavelengths and red wavelengths with varying antenna widths. Our analysis indicates that three coupled modes of surface plasmon polariton and gap surface plasmon are crucial in complex modulation for blue, green, and red color wavelengths, respectively.